Net efficiency of roller skiing with a diagonal stride - Nakai, A.; Ito, A. (Journal of Sports Sciences, 2011)
The aims of this study were: (a) to determine net efficiency during roller skiing with a diagonal stride at various speeds; (b) to assess the development of net efficiency across speeds; and (c) to examine the characteristics of efficiency in diagonal roller skiing. Two-dimensional kinematics and oxygen uptake were determined in eight male collegiate cross-country ski athletes who roller skied with the diagonal stride at various speeds on a level track. Net efficiency was calculated from rates of internal and external work and net energy expenditure. Individual net efficiency ranged from 17.7% to 52.1%. Net efficiency in the entire group of athletes increased with increasing speed, reached a maximum value of 37.3% at 3.68 m/s, before slowly decreasing. These findings indicate that roller skiing with the diagonal stride at high speed is a highly efficient movement and that an optimal speed exists at which net efficiency can be maximally enhanced in diagonal roller skiing.